Impact of Thyroid Hormone Receptor alpha Expression and PD-L1 on Progression-Free Survival of NSCLC Patients Treated with Pembrolizumab Immunotherapy - Leelo Al-Obaidy, Abdulameer Kareem.; A. Kareem, Hawraa; Jabbar Hasan, Yusra (Journal of Neonatal Surgery, 2025)
Lung cancer is categorized into small cell lung cancer and non-small cell lung cancer (NSCLC) based on histological distinctions. Pembrolizumab, an anti-programmed death-1 (PD-1) monoclonal antibody, is utilized for patients with NSCLC who exhibit modulation of the programmed death ligand (PD-L1) molecule. This study prospectively examined different patterns of Thyroid Hormone Receptor (THR) and PD-L1 immunohistochemical expression and their impact on the effectiveness of immunotherapy in improving progression-free survival (PFS) in 93 NSCLC patients. Variations were assessed according to histopathological subtype, TNM staging, tumor grade, Eastern Cooperative Oncology Group (ECOG) performance status, and other factors that may influence disease progression or treatment outcomes. The mean age of patients was 59.97 years, comprising 26 females and 67 males. Among the 93 patients, 55 exhibited low PD-L1 expression (≤10%), while 38 patients exhibited high PD-L1 expression (>10%). THRα expression was observed at variable ratios, and the mean PFS was 48.9 weeks. A significant correlation was found between PD-L1 and THRα regarding PFS, with the highest PFS observed in patients exhibiting THRα expression levels between 26% and 50%, and the lowest PFS duration seen in patients with 76% to 100% THRα expression. The impact of PD-L1 expression on PFS duration increased with elevated levels of PD-L1 expression. These findings demonstrate that THRα and PD-L1 expression are more prevalent in NSCLC patients, correlating with higher tumor grades, increased metastasis, and reduced ECOG performance status. The study found that the PFS of PD-L1-positive NSCLC patients treated with pembrolizumab was significantly better in those with 26% to 50% THR expression.